ANALYSIS OF THE RELATIONSHIP BETWEEN TRAINING AND EMPLOYEE PRODUCTIVITY IN RESTA URANTS IN SURABAYA - Agung Hermawan Febrianto; Achmad Daengs GS; Enny Istanti; Satrio Budiyanto; Halim Soegeng Suprayitno (PT. Mawadaku Sukses Solusindo, 2025)
Service activities in a company cannot be carried out by just one person, but rather by people with different educational backgrounds, experiences, socio-economic statuses, and so on, who work together in the same environment and aim to achieve good productivity. Therefore, the company must involve individuals with various skill levels. In facing today's high competition, companies are required to work professionally in order to provide the best service to consumers, as well as to work effectively and efficiently to generate high income. Realizing this, it is time for individuals within the company to work harder, become more skilled, and have high motivation to achieve. The data used in this research are secondary data, obtained by reviewing sales target data and results achieved each month by the McDonald's restaurant on Mayjend Sungkono Street, Surabaya. Based on the correlation test results, it is known that the simple correlation coefficient (r) shows a value of 0.99, which is close to 1, so it can be concluded that there is a strong and positive relationship between variable X (training) and Y (work productivity).